Persepsi Guru terhadap Perubahan Kurikulum 2013 ke Kurikulum Merdeka : Studi Kasus di Madrasah Ibtidaiyah - Hamriani; Mirnawati; Sukmawaty (South Sulawesi Education Development, 2025)
This study aims to: examine teachers’ perceptions of the Merdeka Curriculum; identify teachers’ understanding of its structure and implementation principles; describe the strategies applied by teachers in implementing the curriculum; and illustrate teachers’ expectations regarding the sustainability of Merdeka Curriculum implementation at the primary education level. The research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving teachers at the madrasah. The findings indicate that teachers hold generally positive perceptions of the Merdeka Curriculum, recognizing it as more flexible and student-centered. However, teachers’ understanding remains varied, particularly in the technical aspects of lesson planning. The strategies used include teacher collaboration, the use of local media, and contextual project-based learning. Teachers also demonstrated creativity in overcoming limited resources. Furthermore, they expressed the need for ongoing training, adequate learning facilities, and strong collaboration among schools, parents, and the government. These findings reflect teachers’ dedication to supporting the ongoing educational reform.